Standardized Forearm Angiography Increases Procedural Success Rates of Coronary Angiography and PCI: A Retrospective Analysis of an all-Comers Patient Cohort in a Real-Life Scenario - Tobias, Roeschl; M, Jano Anas; Franziska, Fochler; M, Grewe Mona; Marlis, Wacker; Kirstin, Meier; Christian, Schmidt; Lars, Maier; H, Grewe Peter (Cardiology and Cardiovascular Medicine, 2022)
Background: There is a consensus, that Transradial-Access (TRA) for coronary procedures should be preferred over Transfemoral-Access (TFA). Previously, Forearm-Artery-Angiography (FA) was mainly performed when difficulties during the advancement of the guidewire/-catheter were encountered. We explored the implication of a Standardized Forearm-Angiography (SFA) on procedural success rates of TRA under real-world conditions. Methods: In a single-center study, an all-comers-cohort of 1191 consecutive cases during 1/2020-12/2020 were assessed retrospectively. Primary TFA rates, crossover to TFA, reasons for Forearm-Artery-Access (FAA) failure, the prevalence of kinking at the level of the forearm and the occurrence of vascular complications were analyzed. Major forearm side branches including the common interosseus artery were assessed via SFA. Results: In 1191 consecutive procedures, primary FAA access was attempted in 97.9% of cases. Crossover to TFA after a primary or secondary FAA attempt was necessary in 2.8%. Severe kinking was the most frequent cause of FAA failure and occurred in 3.0% of attempts. A second or third FAA attempt to avoid TFA was successful in 81%. Severe kinking at the level of the forearm was reported in 1.8% of procedures. Conclusion: This is the first study to provide detailed success rates of a primary FAA strategy combined with a Standardized-Forearm-Angiography (SFA) in an all-comers-cohort. While severe kinking proved to be a rare but relevant challenge for FAA success, the prevalence of arterial spasm was marginal. Multiple attempts of FAA to avoid TFA might be safe possibly due to collateral blood supply by the common interosseus artery.